2018
DOI: 10.1371/journal.pone.0209996
|View full text |Cite
|
Sign up to set email alerts
|

The influence of subretinal injection pressure on the microstructure of the monkey retina

Abstract: PurposeTo investigate the influence of subretinal injection pressure on the microstructure of the retina in a monkey model.MethodsAfter vitrectomy, balanced salt solution was injected subretinally into one eye each of four cynomolgus monkeys while controlling the injection pressure. Initially, a pressure of 2 psi was used, and this was gradually increased to determine the minimum required pressure. Subsequent injections were performed at two pressures: minimum (n = 13) and high (n = 6). To compare the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
(43 reference statements)
3
22
0
1
Order By: Relevance
“…Dose-dependent outer retinal changes with demelanization of the RPE have been reported after the administration of different vector constructs in NHPs, as well as after injection of control balance salt solutions 37, 43, 47, 48. These vector-independent abnormalities may be the consequence of low grade, immune-mediated responses within the subretinal space triggered by exposure of foreign proteins that may not be detected by the immune assays used in this work or by routine histopathology.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Dose-dependent outer retinal changes with demelanization of the RPE have been reported after the administration of different vector constructs in NHPs, as well as after injection of control balance salt solutions 37, 43, 47, 48. These vector-independent abnormalities may be the consequence of low grade, immune-mediated responses within the subretinal space triggered by exposure of foreign proteins that may not be detected by the immune assays used in this work or by routine histopathology.…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, the administration of rAAV2- hRPE65v2 to NHPs produces pigmentary changes within the blebs visible by fundus exam, which can be used to precisely locate a second subretinal injection in relationship to a previous one. In one animal (two eyes), a readministration of the treatment was at a site distant from the first injection to exclude mechanical (surgery-related) effects on the initially injected retina; in the other two animals, the treatment was delivered so that there was a partial or total overlap between the first and second injections 13, 43. The experiments demonstrated that ipsilateral readministration to the NHP retina was safe from an immunologic standpoint, even when readministration location coincided nearly exactly with the initially treated retinal area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one case, an intraoperative foveal perforation occurred at injection pressure greater than 20psi. For the remaining cases, we did not encounter any cases of foveal perforation at an injection pressure of 20psi or less [15]. In the one case of macular hole observed during chip implantation, the PRIMA microchip was implanted in the subretinal space.…”
Section: Discussionmentioning
confidence: 91%
“…3.) Senken des Druckes der Infusionsflasche auf < 20 mmHg, sodass der Augeninnendruck niedrig ist und der Widerstand gegen die Netzhaut nicht kĂŒnstlich erhöht wird [11]…”
Section: Schritt Cunclassified